Predictors of low-intensity laser radiation effectiveness in patients with unstable angina - V. V. Belov; U. V. Kharlamova (Российский кардиологический журнал, 2008)
In total, 100 men with unstable angina (UA) were randomized into two groups, comparable by age, cardiovascular anamnesis and treatment. The intervention group (n=49) received low-intensity laser radiation (LDLR) therapy, the control group (n=51) - placebo intervention. Parameters of free-radical oxidation, nitroxidergic system, and lipid profile were assessed at Days 2 and 9. Physical stress tolerance (PST) was assessed at Days 16-18, by veloergometry. In UA patients, LILR was associated with substantial decrease in atherogenic lipid profile parameters, normalization of TBA-active product levels, nitrite concentration increase, as well as significant PST improvement inpatients with Class II-II UA.